Myocardial inflammation, sports practice, and sudden cardiac death: 2021 update - Compagnucci, P.; Volpato, G.; Falanga, U.; Cipolletta, L.; Conti, M. A.; Grifoni, G.; Ciliberti, G.; Stronati, G.; Fogante, M.; Bergonti, M.; Sommariva, E.; Guerra, F.; et al. (Medicina, 2021)
Myocardial inflammation is an important cause of cardiovascular morbidity and sudden cardiac death in athletes. The relationship between sports practice and myocardial inflammation is complex, and recent data from studies concerning cardiac magnetic resonance imaging and endomyocardial biopsy have substantially added to our understanding of the challenges encountered in the comprehensive care of athletes with myocarditis or inflammatory cardiomyopathy (ICM). In this review, we provide an overview of the current knowledge on the epidemiology, pathophysiology, diagnosis, and treatment of myocarditis, ICM, and myopericarditis/perimyocarditis in athletes, with a special emphasis on arrhythmias, patient-tailored therapies, and sports eligibility issues.